SIMULATOR DEVELOPMENT OF NON INVASIVE MEASUREMENT OF HEMOGLOBIN CONCENTRATION BASED ON GIANT MAGNETORESISTANCE - AMINUDIN (NIM: 30211002), AHMAD
Research and simulator development of non-invasive measurement of hemoglobin concentration based on giant magnetoresistance. The purpose of this study designed and developed the simulator measurement of hemoglobin concentration in a non invasive based on the magnetic properties of hemoglobin. The specific objectives of the research are: 1) Develop a circuites of giant magnetoresistance (GMR) sensors for measuring weak magnetic fields, 2) Design and create a source of strong magnetic field for intrumentation system, 3) Develop of signal amplifier and signal processor analog sensor GMR, 4) Design a model of generator for the fluid flow in the blood vessels, 5) Measuring devices to create a prototype non-invasive hemoglobin levels, and 6) Testing to determine the ability of sensor for sensing the concentration of ferric chlorite, porphyrin and hemoglobin. Simulator design is made to get the hemoglobin concentration measurement model without taking blood samples (non-invasive). The Simulator measurement is consists of a sample, fluid flow generator, a permanent magnet, GMR sensor, signal amplifier, ADC, processing unit, display and personal computer (PC). Plants will drain the fluid flow is controlled solution, then the solution will be magnetized by the permanent magnet. While the solution is flowing below the GMR sensor, solution will be responded by the GMR sensor. GMR sensor output signal is amplified by a signal amplifier which then is converted into a digital signal to be easily processed. Response of GMR sensor voltage to the magnetic field 1,1 T versus distance variation on the X-axis direction indicates the saturation voltage 372.3 mV at a distance of 2 cm and cut-off voltage 29.3 mV at a distance of 10 cm to finally shows a voltage of 21.8 mV at a distance of 22 cm. On the Y-axis direction, testing GMR sensor response indicates the saturation voltage 373.0 mV at a distance of 3 cm and cut-off voltage 21.8 mV at a distance of 22 cm. This indicates that the GMR sensor placement after passing a distance of 10 cm in the direction of the X and Y directions 22 cm, can be recommended as the limit value in design of the measurement of the fluid flow magnetic field. Results of testing the amplification factor of amplifier circuit indicates that the gain setting 10 times gained 9.5 Ã‚Â± 1.2, and the gain setting 100 times obtained 97.3 Ã‚Â± 0.8. In granting greater input voltage 50mV produces saturated output voltage (relatively constant) is 4.26 V for truncated source voltage Vcc of ICAD524. Results of tests the current-voltage characteristics of a DC motor with no load roller indicates that the input voltage of 0.5 V, DC motor is not spinning and start spinning when the input voltage is 1.0 V. granted after passing a DC motor Flow increased 0.10 A any increase in voltage 1 V. input current-voltage characteristics of DC motor with the load roller indicates that the input voltage is less from 1.5 V, dc motor is not spinning and start spinning when the input voltage is 1.5 V. DC motor current increases 0.08 A any increase in the input voltage 1 V. Characterization of the angular velocity of the control voltage shows that the average response of the angular velocity of the gear-1 at 3.939 rpm/Volt and 2nd gear at 1.313 rpm/Volt for every increase 1 Volt. The test results obtained by the value of the volume flow rate sensitivity of 1.429 x 10-3 mL/Volt based on the calculation and 1.431 x 10-3 mL/Volt based measurements. The results of these tests applied to test the GMR sensor response to concentration FeCl3 solution with a flow rate of 3.42 cm/s obtained a sensitivity of 0.056 mV/lm. GMR sensor response relationship to porphyrin concentrations are influenced by the flow rate. The test results showed that the flow rate of the porphyrin 3.42 cm/s, 3.66 cm/s, 3.78cm/s, 3.94 cm/s 3.99 cm/s have sensitivity 0.13 mV/μM. It shows more and more solution volume shows the volume of the magnetic moment more so the greater the value of magnetization. Values greater magnetization generates a magnetic field which is great so the greater sensing GMR sensor. These results also show the GMR sensor capable of responding consentration porphyrins on the order of micro mollar. Characterization of GMR sensor voltage against variations in hemoglobin levels with a flow rate indicates that the flow rate of 0.29 cm/s GMR sensor sensitivity of 20.22 mV/(g/dL), the flow rate of 0.31 cm/s sensitivity of 20.34 mV/(g/dL), at a flow rate 0.33 cm/s, the GMR sensor sensitivity to hemoglobin of 20.45 mV/(g/dL), at a flow rate of 0.35 cm/s. GMR has a sensitivity of 20.59 mV/(g/dL) and at a flow rate of 0.37 cm/s obtained a sensitivity of 20.95 mV/(g/dL). The flow rate increases responded by GMR sensor with greater sensitivity. Increase in the flow rate of the GMR sensors respond with greater sensitivity. The faster the flow rate cause hemoglobin volume per second GMR sensors to feel more and more. Volume of hemoglobin increasingly affect the volume of the magnetic moment of hemoglobin, so the greater the value of the magnetization. Magnetization larger value generates a magnetic field which is great so the greater the GMR sensor taste. Overall, the measurement of the concentration of simulator development is a non-invasive hemoglobin-based giant magnetoresistance has been successfully created. Simulator measurement uses of a flow rate of 0.05 to 0.4 cm/s to represent the flow velocity in the blood vessel capillaries is about 0.1 cm/s which is constant. To obtain an oscillating flow rate as in large blood vessels (aorta and vena cava) requires the development of plants which oscillates flow rate follows the human heart rate.